The prognosis model of treatment efficiency for pulmonary tuberculosis in intensive phase of antituberculosis therapy - Hovardovska, Olga; Schevchenko, Olga; Arseniev, Olexandr (ScienceRise: Medical Science, 2018)
Search of ways to improve the treatment efficacy of pulmonary tuberculosis is the main task of phthisiology at the present stage of its development. According to our opinion, one of such way is the prediction of outcomes of anti-tuberculosis therapy intensive phase at its initial stage, which will allow to make correction of the treatment regimen opportunely. The aim of the study was to determine informative indicators for predicting the efficacy of treatment of patients with pulmonary tuberculosis in the intensive phase of anti-tuberculosis therapy. Based on the results, to create a model for predicting the efficacy of treatment for tuberculosis in the intensive phase for the correction of the treatment regimen. Materials and methods: 80 patients with active pulmonary tuberculosis, which were registered in categories 1 and 2, were examined. The patients were divided into groups: the first group of 30 patients with positive effect, the second group of 50 patients with delayed or negative treatment effect at the end of the intensive phase. The control group consisted of 20 healthy individuals. The sampling of diagnostic material was performed at the beginning of therapy. The results of clinical analysis of blood, as well as serum levels of neopterin, C-reactive protein, creatinine, ceruloplasmin, haptoglobin, seromukoid were evaluated. To achieve this goal, the nonparametric χ2 criterion and correspondent analysis were used. Results: There are 3 parameters with threshold values identified, which could be transformed into dichotomous indicators, of the 11 studied indices. These 3 variables are: the proportion of lymphocytes in the leukocyte formula, the content of neopterin, and seromucoids in the serum. Using correspondence analysis method, the formula to predict the result of the intensive phase from the initial values of the indicated variables was derived. Approbation of the formula showed high prediction accuracy (>80 %) for both groups. Conclusions: With the help of the developed formula, which takes into account the initial indicators of serum neopterin and seromucoid and the proportion of lymphocytes in the leukocyte formula, the efficacy of treatment of pulmonary tuberculosis in the intensive phase of tuberculosis therapy can be predicted